2021
DOI: 10.1101/2021.07.12.21260208
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Daily sampling of early SARS-CoV-2 infection reveals substantial heterogeneity in infectiousness

Abstract: The dynamics of SARS-CoV-2 replication and shedding in humans remain poorly understood. We captured the dynamics of infectious virus and viral RNA shedding during acute infection through daily longitudinal sampling of 60 individuals for up to 14 days. By fitting mechanistic models, we directly estimate viral reproduction and clearance rates, and overall infectiousness for each individual. Significant person-to-person variation in infectious virus shedding suggests that individual-level heterogeneity in viral d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 61 publications
5
48
1
Order By: Relevance
“…However, most studies to date base their conclusions on cross sectional sampling of viral genome loads (as measured by RTqPCR), which may not directly translate to infectiousness 6 . In a cohort of longitudinally sampled participants who screened positive for SARS-CoV-2, we previously showed that the relationship between viral genome load and infectious virus load can vary greatly across individuals and over time, making the use of cross-sectional RTqPCR data problematic for estimations of infectiousness 7 . Therefore, longitudinal comparisons of viral genome shedding and infectious virus shedding across tissue compartments between vaccinated and unvaccinated individuals are needed to more accurately assess the effects of vaccination on viral dynamics and transmission potential.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most studies to date base their conclusions on cross sectional sampling of viral genome loads (as measured by RTqPCR), which may not directly translate to infectiousness 6 . In a cohort of longitudinally sampled participants who screened positive for SARS-CoV-2, we previously showed that the relationship between viral genome load and infectious virus load can vary greatly across individuals and over time, making the use of cross-sectional RTqPCR data problematic for estimations of infectiousness 7 . Therefore, longitudinal comparisons of viral genome shedding and infectious virus shedding across tissue compartments between vaccinated and unvaccinated individuals are needed to more accurately assess the effects of vaccination on viral dynamics and transmission potential.…”
Section: Main Textmentioning
confidence: 99%
“…(C) Same data as in (A) but for newly vaccinated individuals that enrolled < 14 days after first mRNA or J&J vaccine dose. (D) Numbers of days that vaccinated (combined fully and partially vaccinated individuals), newly vaccinated individuals, and unvaccinated individuals (from Ke et al 7 ) tested viral culture positive. ns, p>0.05; * p<0.05; ** p<0.01; *** p<0.001.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Both models were calibrated to provide realistic incubation period distributions (Supplementary Figure 1), similar distributions of generation time for symptomatic individuals (Supplementary Figure 2) and time from onset of symptoms to transmission (Supplementary Figure 3). The viral load dynamics are assumed to be similar for all viral strains (Kissler, Fauver, Mack, Tai, et al 2021;Ke et al 2021).…”
Section: An Integrated Model For Covid-19 Transmission Dynamicsmentioning
confidence: 99%
“…While viral loads can vary across individuals, with some shedding more than others 7 , the mean distribution of viral loads from a group of patients measured around the time of illness onset will tend to have higher values than that of viral loads from a group of patients measured at a later time after infection 8 . Collectively, higher population-level viral loads would correlate with more infected persons being earlier in the course of infection and vice versa 9 .…”
Section: Introductionmentioning
confidence: 97%